From parallel practice to integrative health care: a conceptual framework - O'Hara Dennis; Verhoef Marja; Boon Heather; Findlay Barb (BMC Health Services Research, 2004)
Abstract Background "Integrative health care" has become a common term to describe teams of health care providers working together to provide patient care. However this term has not been well-defined and likely means many different things to different people. The purpose of this paper is to develop a conceptual framework for describing, comparing and evaluating different forms of team-oriented health care practices that have evolved in Western health care systems. Discussion Seven different models of team-oriented health care practice are illustrated in this paper: parallel, consultative, collaborative, coordinated, multidisciplinary, interdisciplinary and integrative. Each of these models occupies a position along the proposed continuum from the non-integrative to fully integrative approach they take to patient care. The framework is developed around four key components of integrative health care practice: philosophy/values; structure, process and outcomes. Summary This framework can be used by patients and health care practitioners to determine what styles of practice meet their needs and by policy makers, healthcare managers and researchers to document the evolution of team practices over time. This framework may also facilitate exploration of the relationship between different practice models and health outcomes.